Analisis Kepatuhan Higiene Penjamah Makanan dan Sanitasi Peralatan di Whitespoon Catering Malang - Firjatulloh, Muhammad Bachtiar; Kholidah, Diniyah (NUTRITURE JOURNAL, 2024)
Background: Food handler compliance with Standard Operating Procedures (SOP) for hygiene and the condition of kitchen equipment sanitation plays a crucial role in ensuring food safety. However, adherence to SOPs often becomes a challenge, especially in the catering sector. Objective: This study aimed to analize food handler compliance and kitchen equipment sanitation at Whitespoon Catering based on regulatory standards. Design: The study used a cross-sectional descriptive design and implementation evaluation, with data collection methods including observations, structured interviews, and questionnaires. Results: The findings showed that most food handlers’ compliance levels were in the "moderate" category, with the main weakness being the use of personal protective equipment (PPE). Kitchen equipment sanitation revealed the greatest gap in the storage aspect, which only met 50% of the standard. Statistical analysis indicated a significant relationship between work experience and compliance levels, while formal education had no significant effect. Conclusions: The compliance of food handlers with SOP hygiene requires improvement, particularly in the use of PPE. In addition, kitchen equipment sanitation needs enhancement, prioritizing storage management. These findings can be used to promote practice-based training, regular supervision, and infrastructure improvements to enhance food safety in the catering sector.